Spatio-temporal evolution and influencing factors of coupling coordination between urban resilience and high-quality development in Yangtze River Delta Area, China - Zhang, Jie; Yuan, Jiade; Wang, Yuchun (Frontiers in Environmental Science, 2023)
The coordination relationship between urban resilience and high-quality development is of paramount importance for improving disaster-alleviated resilient governance and sustainable development in response to the globalized crisis. Accordingly, we adopted the entropy method, coupling coordination model, kernel density estimation curve and spatial econometric models, to analyze the spatio-temporal patterns and influencing factors of the coupling coordination degree (CCD) between urban resilience and high-quality development in the Yangtze River Delta Area (YRDA) from 2005 to 2020. The results revealed that urban resilience maintained a steady growth, while high-quality development displayed a trend of an initial increase and a subsequent decline. The CCD continued to rise and the regional difference decreased conspicuously, manifesting a robust developing trend. From the perspective of spatial patterns, the CCD, which was characterized by "being high in the east and low in the west, tended to be balanced in the north and south and was prominent in the middle of the distribution". Furthermore, economic strength, industrial structure, transportation facilities, and government intervention exerted a dominant influence on the development of CCD , resulting in the spatial spillover effects as well. This study can reveal the interactive relationship between urban resilience and high-quality developmentcan as well as help YRDA provide a benchmark for promoting economic and social development while focusing on prevention and control of risk.